Determining the Wave Vector Direction of Equatorial Fast Magnetosonic Waves - Scott A. Boardsen; George B. Hospodarsky; Kyungguk Min; Terrance F. Averkamp; Scott R. Bounds; Craig A. Kletzing; Robert F. Pfaff (Geophysical Research Letters)
Abstract We perform polarization analysis of the equatorial fast magnetosonic waves electric field over a 20‐min interval of Van Allen Probes A waveform receiver burst mode data. The wave power peaks at harmonics of the proton cyclotron frequency indicating that the spacecraft is near or in the source region. The wave vector is inferred from the direction of the major axis of the electric field polarization ellipsoid and the sign of the phase between the longitudinal electric and compressional magnetic field components. We show that wave vector is preferentially in the azimuthal direction as opposed to the radial direction. From Poynting flux analysis one would infer that the wave vector is primarily in the radial direction. We show that the error in the Poynting flux is large ~90°. These results strongly imply that the wave growth occurs during azimuthal propagation in the source region for this event.